Standard operating procedure for starting and disassembling single solid oxide cells for testing in electrolysis mode - Belko, Seraphim; Springer, Renaldo; Le, Long; Coyle, Christopher A.; Marina, Olga A. (Frontiers in Energy Research, 2025)
Presented is a simple, step-by-step methodology describing how to start, precondition, terminate testing, and disassemble single, small-sized planar electrode-supported solid oxide electrolysis cells (SOECs). Careful control of the gas environment in the initial and final stages of solid oxide cell testing is essential for establishing baseline performance, ensuring controlled, reproducible electrochemical performance, and preserving cell chemical and structural integrity for post-mortem analyses.